Customer Relationship Management (CRM) Training in Increasing Business Sales During the Covid-19 Pandemic: Customer Relationship Management (CRM) Training in Increasing Business Sales During the Covid-19 Pandemic - Hakim, Adi Lukman; Fajri, Mega Barokatul; Faizah, Erna Nur (CV. Inara, 2021)
The Covid-19 pandemic demands that businesses go digital. Not only products must be marketed through technology, but the way of communication with consumers must also be arranged systematically to stabilize income. Among a number of tools designed to answer customer retention demands, CRM software was chosen because this tool can accommodate consumer data, business data, track consumer interactions, and track company prospects. The purpose of this activity is to conduct training and assistance in implementing Customer Relationship Management in increasing sales during the pandemic. This method uses a descriptive qualitative approach with training design in using Customer Relationship Management software. Instruments in the form of learning experience and literature study. This community partnership program involves business start-ups within the Muhammadiyah University of Lamongan, especially students majoring in Accounting and Management. The results of this study indicate that the application of CRM has an effect as an effort to increase business sales during the pandemic with a series of strategic CRM processes, operational CRM, analytical CRM. Essentially, both upper, middle, and even lower customers need good and quality service, it's just that the levels are different. When start-up actors apply the right and good CRM, it will automatically increase customer satisfaction which has an impact on increasing business sales.